Cell membrane stability - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
A simple test for evaluating membrane stability is briefly described. In a comparison of 12 lines representing groups identified for cold, drought, or heat tolerance, cold tolerance was associated with greater membrane damage, and heat-tolerant materials showed the least damage. Drought-tolerant materials showed an intermediate level, which suggests that this group is not unusually heat tolerant, as some researchers had hypothesized. Preliminary data indicate that membrane stability or related techniques may provide a powerful tool for screening germplasm for temp. adaptation or drought tolerance. The technique is nondestructive, could easily be standardized, and appears to measure a basic characteristic of plant response to environment. (CIAT)